Beispiel Nr: 02
$\text{Gegeben:}\\\text{Länge} \qquad a \qquad [m] \\ \text{Breite} \qquad b \qquad [m] \\ \text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Höhe} \qquad c \qquad [m] \\ \\ c = \frac{O-2\cdot b\cdot a}{2\cdot (b+a)}\\ \textbf{Gegeben:} \\ a=4m \qquad b=7m \qquad O=1m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ c = \frac{O-2\cdot b\cdot a}{2\cdot (b+a)} \\ a=4m\\ b=7m\\ O=1m^{2}\\ c = \frac{1m^{2}-2\cdot 7m\cdot 4m}{2\cdot (7m+4m)}\\\\c=-2\frac{1}{2}m \\ \small \begin{array}{|l|} \hline a=\\ \hline 4 m \\ \hline 40 dm \\ \hline 400 cm \\ \hline 4\cdot 10^{3} mm \\ \hline 4\cdot 10^{6} \mu m \\ \hline 0,004 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 7 m \\ \hline 70 dm \\ \hline 700 cm \\ \hline 7\cdot 10^{3} mm \\ \hline 7\cdot 10^{6} \mu m \\ \hline 0,007 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline O=\\ \hline 1 m^2 \\ \hline 100 dm^2 \\ \hline 10^{4} cm^2 \\ \hline 10^{6} mm^2 \\ \hline 0,01 a \\ \hline 0,0001 ha \\ \hline 10^{-6} km^2 \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline c=\\ \hline -2,5 m \\ \hline -25 dm \\ \hline -250 cm \\ \hline -2,5\cdot 10^{3} mm \\ \hline -2,5\cdot 10^{6} \mu m \\ \hline -0,0025 km \\ \hline \end{array}\\$